2000
DOI: 10.1093/nar/28.9.1899
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific modification and RNA crosslinking of the RNA-binding domain of PKR

Abstract: RNA-dependent protein kinase (PKR) is an interferon-induced, RNA-activated enzyme that phosphorylates and inhibits the function of the translation initiation factor eIF-2. PKR is activated in vitro by binding RNA molecules with extensive duplex structure. To further define the nature of the RNA regulation of PKR, we have prepared and characterized site-specifically modified proteins consisting of the PKR 20 kDa RNA-binding domain (RBD). Here we show that the two cysteines found naturally in this domain can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Our technique generates ∼100 µg purified dephosphoPKR per liter of culture whose in vitro The advent of a technique for generating wild-type PKR in a dephosphorylated state allowed us to directly assess the effect of autophosphorylation on RNA binding affinity. The discovery of autophosphorylation sites in the dsRBD of PKR and the observation that one of those sites is near the protein/ RNA interface in a complex between the dsRBD and an RNA activator led us to speculate that phosphorylation could influence the RNA-binding properties of the enzyme (23,24,26). This is consistent with previous reports indicating that once autophosphorylated, PKR no longer responds to RNA regulators, including kinase inhibiting RNAs (41).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our technique generates ∼100 µg purified dephosphoPKR per liter of culture whose in vitro The advent of a technique for generating wild-type PKR in a dephosphorylated state allowed us to directly assess the effect of autophosphorylation on RNA binding affinity. The discovery of autophosphorylation sites in the dsRBD of PKR and the observation that one of those sites is near the protein/ RNA interface in a complex between the dsRBD and an RNA activator led us to speculate that phosphorylation could influence the RNA-binding properties of the enzyme (23,24,26). This is consistent with previous reports indicating that once autophosphorylated, PKR no longer responds to RNA regulators, including kinase inhibiting RNAs (41).…”
Section: Discussionsupporting
confidence: 86%
“…1; 23,24). Furthermore, one of these residues (S33) has been shown to be in proximity to the RNA in the bound complex (26). These results suggested that autophosphorylation may have an effect on the RNAbinding properties of the enzyme (26).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations